CLASSIFICATION AND USE OF EMITTERS USED IN SPRAY IRRIGATION SYSTEMS - Rocha, Mayara O.; Cunha, Fernando F. da; Viana, Felipe J.; Oliveira, Job T. de (Engenharia agrícola, 2023)
ABSTRACT This efficiency in the application of water is associated with the evolution of irrigation equipment and systems and can be illustrated by the drippers in the case of localized irrigation, the sprinklers in the case of sprinkler irrigation, and the low-pressure emitters used in a central pivot. Given the context presented, this study aimed to carry out a theoretical approach on the classification and use of emitters used in pressurized sprinkler irrigation systems, carrying out bibliographical research on the subject. The research is exploratory, where articles and books with related subjects were researched: “classification and use of emitters used in pressurized sprinkler irrigation systems”. The research was carried out via the Google Academic platform and in libraries. The type of emitter to be chosen depends on many factors that influence the efficiency of the system. Therefore, a well-designed project, with the correct choice of the type of emitter, maximizes the application efficiency, minimizes energy expenditure, and increases the producer's profitability.